Zebrafish stm is involved in the development of otoliths and of the fertilization envelope - Theeranukul Pachoensuk; Taketo Fukuyo; Md. Rezanujjaman; Klangnurak Wanlada; Chihiro Yamamoto; Akiteru Maeno; Md. Mostafizur Rahaman; Md. Hasan Ali; Toshinobu Tokumoto (Bioscientifica, 2021)
Using an in vivo assay, we selected 11 genes that were highly upregulated during the induction of ovulation in zebrafish using microarray analysis and RNA sequencing. The starmaker gene (stm) was one of these genes. Although stm has been previously reported to be involved in otolith formation during the early development of zebrafish, we detected its expression in eggs and showed that stm was related to fertilization by establishing an stm gene knockout strain using the CRISPR/Cas9 system. Further phenotypic analysis of stm knockout fish was conducted in this study. With a higher nonfertilization rate, the stm mutant strain showed an extremely low survival rate. Otoliths of stm homozygous mutant zebrafish showed abnormal morphology in embryos and adult fish. However, fish did not show any abnormalities in swimming behaviour in either embryos or adults. Stm proteins were detected on the chorion of ovulated eggs before spawning. Fibre-supported knob-like structures on the fertilization envelope (FE) also showed abnormal structures in stm mutants. The Stm protein is necessary for otolith formation, and a lack of Stm causes abnormal otolith formation. The partial defect of otolith formation does not cause defects in swimming behaviour. The Stm protein is expressed in the chorion and is responsible for the formation of fibre-supported knob-like structures on the FE. It was suggested that a lack of Stm caused a lower fertilization rate due to inadequate formation of the FE.